Insulin-Like Growth Factor-1 Receptor Deficiency in Macrophages Accelerates Atherosclerosis and Induces an Unstable Plaque Phenotype in Apolipoprotein E–Deficient Mice. Issue 23 (7th June 2016) - Higashi, Yusuke; Sukhanov, Sergiy; Shai, Shaw-Yung; Danchuk, Svitlana; Tang, Richard; Snarski, Patricia; Li, Zhaohui; Lobelle-Rich, Patricia; Wang, Meifang; Wang, Derek; Yu, Hong; Korthuis, Ronald; et al.
Abstract : Background—: We have previously shown that systemic infusion of insulin-like growth factor-1 (IGF-1) exerts anti-inflammatory and antioxidant effects and reduces atherosclerotic burden in apolipoprotein E (Apoe)–deficient mice. Monocytes/macrophages express high levels of IGF-1 receptor (IGF1R) and play a pivotal role in atherogenesis, but the potential effects of IGF-1 on their function are unknown. Methods and Results—: To determine mechanisms whereby IGF-1 reduces atherosclerosis and to explore the potential involvement of monocytes/macrophages, we created monocyte/macrophage–specific IGF1R knockout (MΦ-IGF1R-KO) mice on an Apoe −/− background. We assessed atherosclerotic burden, plaque features of stability, and monocyte recruitment to atherosclerotic lesions. Phenotypic changes of IGF1R-deficient macrophages were investigated in culture. MΦ-IGF1R-KO significantly increased atherosclerotic lesion formation, as assessed by Oil Red O staining of en face aortas and aortic root cross-sections, and changed plaque composition to a less stable phenotype, characterized by increased macrophage and decreased α-smooth muscle actin–positive cell population, fibrous cap thinning, and decreased collagen content. Brachiocephalic artery lesions of MΦ-IGF1R-KO mice had histological features implying plaque vulnerability. Macrophages isolated from MΦ-IGF1R-KO mice showed enhanced proinflammatory responses on stimulation by interferon-γ and oxidized low-density lipoprotein and elevated antioxidant gene expression levels. Moreover, IGF1R-deficient macrophages had decreased expression of ABCA1 and ABCG1 and reduced lipid efflux. Conclusions—: Our data indicate that macrophage IGF1R signaling suppresses macrophage and foam cell accumulation in lesions and reduces plaque vulnerability, providing a novel mechanism whereby IGF-1 exerts antiatherogenic effects. Abstract : Supplemental Digital Content is available in the text.